Evaluation Microbiologique Et Origines De La Contamination Des Produits De 4Ã¨me Gamme Vendus Sur Les MarchÃ©s Dâ€™abidjan, Cote D’ivoire - Anin, Louise Atchibri; Assoi Yapi, Patrice DÃ©sirÃ© Yapi; Monnet, Yapo Thierry; Yiwo Yapi, Marie-Ange; Soro, Chantal LÃªnifÃ©rÃ©; Kouadio, K.A Kouakou (European Scientific Journal, ESJ, 2016)
The sources and degree of microbial contamination of 4 th range products or ready-to-eat products made from traditional processes were evaluated in three markets in the city of Abidjan. This study initially consisted of searching for microorganisms such as Staphylococcus aureus, faecal coliforms, E. coli and Salmonella spp. Then, Ishikawa’s method or diagram was used to determine potential sources of food contamination consisting of three (3) fruit and two (2) fruit vegetables and one (1) leafy vegetable, respectively, pineapple (Ananas comosus) papaya (Carica papaya), watermelon (Citrulus lanatus), onion (Allium cepa), tomato (Lycopersicum esculentum Mill.) and amaranthus (Amaranthus hybridus). Fecal coliform loads were very high at the fruit level (1.8 Ã— 103 - 9.1 Ã— 102 CFU / g), onion (1.3 Ã— 104 CFU / g), tomato puree (1, 82 Ã— 103 CFU / g) and an E. coli load at the tomato puree which is 9.1 Ã— 102 CFU / g. The analysis using the Ishikawa diagram shows that contamination sources were the poor quality of water, raw material, lack of sanitation, illiteracy, unsafe traditional practices and sellers hygiene.